A systematic review of the characteristics of interventions that promote physical activity in adults with asthma. (October 2022) - Tyson, Leanne; Hardeman, Wendy; Marquette, Malcolm; Semlyen, Joanna; Stratton, Gareth; Wilson, Andrew M
Physical activity is promoted in the asthma population through pulmonary rehabilitation, but limited funding and facilities are available. This review aimed to examine the effectiveness of interventions that promote physical activity and identify the behaviour change techniques (BCTs) and other intervention components used. Five databases were searched, and 25 studies met the inclusion criteria. Interventions had a significant positive effect on physical activity, sedentary behaviour, quality of life and asthma symptoms. BCTs used across intervention and control groups were similar in studies that showed effects and those that did not. Future interventions should employ techniques that help to maintain behaviour change.